Electrical conductivity measurement in Thiel‐embalmed tissue model: relevance to radiofrequency ablation. Issue 16 (1st July 2014) - Wang, Zhigang; Luo, Hongyan; Nick, M.; Gueorguieva, M.; Andre, P.; Baker, R.T.; McLean, D.; Brown, S.; Cuschieri, A.
Abstract : Thiel‐embalmed human cadaveric specimens are used widely for biomedical scientific investigation. This Letter reports electrical impedance measurements of Thiel‐embalming solutions from 1 Hz to 32 MHz. Compared with other solutions studied, Thiel solution has the lowest impedance throughout the test spectrum. The electrical conductivity of a Thiel‐embalmed liver sample exhibited a relatively flat frequency response from 100 to 500 kHz, which is the frequency range used for electro‐surgery and radiofrequency tumour ablation (RFA). It measured 5 Sm −1 compared with 0.22 Sm −1 obtained from ex‐vivo fresh pig liver. Using finite element modelling and experimental evaluation, the ablation zone obtained from the Thiel‐embalmed liver sample was extremely small due to its much higher conductivity. Hence, it is concluded that Thiel‐embalmed tissue cannot be used as a reliable model for RFA evaluation.